إنعكاس الاختلاط على حصة التربية البدنية والرياضية (الأستاذ والتلميذ) فيمرحلة التعليم المتوسط - عون الله نبيل (My University, 2025)
الملخص : عنوان الدراسة : دراسة تقويمية للاختلاط وانعكاساته على اداء كل من الاستاذ و التلميذ في حصة التربية البدنية و الرياضية لتلاميذ الاقسام النهائية للطور المتوسط بلدية الدبيلة –ولاية الوادي . هدفت الدراسة إلى :التعرف على انعكاس الاختلاط على اداء كل من الاستاذ و التلميذ في حصة التربية البدنية و الرياضيةلتلاميذ الاقسام النهائية للطور المتوسط مشكلة الدراسة :ما مدى تأثير الاختلاط وانعكاساته على اداء كل من الاستاذ و التلميذ في حصة التربية البدنية و الرياضية لتلاميذ الاقسام النهائية للطور المتوسط فرضيات الدراسة : يمكن صياغة الفرضيات الجزئية كالأتي: • للاختلاط انعكاس سلبي على أداء الأستاذ في حصة التربية البدنية و الرياضية في الطور المتوسط لتلاميذ المرحلة النهائية. • للاختلاط انعكاس سلبي على أداء التلميذ في حصة التربية البدنية و الرياضية في الطور المتوسط لتلاميذ المرحلة النهائية. إجراءات الدراسة الميدانية : العينة : تضم 90 تلميذ و 30 أستاذ للتربية البدنية والرياضية في مقاطعة الوادي –ولاية الوادي- المجال المكاني : متوسطات مقاطعة الوادي –ولاية الوادي- المجال الزماني : امتدت دراستنا من 15 من شهر فيفري إلى النصف الأول من شهر أفريل. المنهج المتبع : المنهج الوصفي. أدوات الدراسة : الاستبيان. النتائج المتوصل إليها: • للاختلاط انعكاس سلبي على أداء التلميذ في حصة التربية البدنية والرياضية لأقسام المرحلة النهائية للطور المتوسط . • للاختلاط انعكاس سلبي على أداء التلميذ في حصة التربية البدنية والرياضية لأقسام المرحلة النهائية للطور المتوسط . الاقتراحات والتوصيات: • ضرورة الاهتمام بحصة التربية البدنية و الرياضية من خلال الحد من الاختلاط اثناء الحصة . • مراعاة التوزيع الزمني في الاسبوع لحصة التربية البدنية و الرياضية بدمج الاقسام من اجل تشكيل افواج للذكور و الاناث . • مراعاة توقيت الحصة خلال ممارسة النشاط لكل جنس من التلاميذ لمساعدة الاستاذ على الاداء . absract : Title of the study: An evaluative study of mixing and its repercussions on the performance of both the teacher and the student in the physical education and sports class for students in the final sections of the intermediate stage-Debila Municipality -El Oued State. The study aimed to: identify the impact of mixing on the performance of both the teacher and the student in the physical education and sports class for students in the final sections of the intermediate stage :Study hypotheses: Partial hypotheses can be formulated as follows • Mixing has a negative impact on the teacher’s performance in the physical education and sports class in the intermediate stage for final stage students. • Mixing has a negative impact on the student’s performance in the physical education and sports class in the intermediate stage for final stage students. Field study procedures: The sample: includes 90 students and 30 teachers of physical education and sports in El Oued Province - El Oued State. Spatial field: averages of El Oued Province - El Oued State - Temporal scope: Our study extended from the 15th of February to the first half of April. The method followed: descriptive method. Study tools: questionnaire. Findings: • Mixing has a negative impact on the student’s performance in the physical education and sports class for the final sections of the intermediate stage. • Mixing has a negative impact on the student’s performance in the physical education and sports class for the final sections of the intermediate stage. Suggestions and recommendations: • The necessity of paying attention to the physical education and sports class by limiting mingling during the class. • Taking into account the time distribution per week for the physical education and sports class by merging the departments in order to form cohorts for males and females. • Taking into account the timing of the class during the activity for each gender of students to help the teacher perform. résumé Titre de l'étude : Étude évaluative des classes mixtes et de leur impact sur les performances des enseignants et des élèves en éducation physique et sportive (EPS) pour les élèves de terminale du collègedela commune de Debila, province d'El Oued. L'étude visait à : Identifier l'impact des classes mixtes sur les performances des enseignants et des élèves en éducation physique et sportive (EPS) pour les élèves de terminale du collège Problème de recherche : Dans quelle mesure la mixité affecte-t-elle les performances des enseignants et des élèves en cours d’éducation physique en terminale ? Hypothèses de recherche : Les hypothèses partielles peuvent être formulées comme suit: • La mixité a un impact négatif sur les performances des enseignants en éducation physique et sportive pour les collégiens. • La mixité a un impact négatif sur les performances des élèves en éducation physique et sportive pour les collégiens. Procédures de l'étude de terrain : Échantillon : 90 élèves et 30 enseignants d'éducation physique et sportive du district d'El Oued, province d'El Oued. Champ d'application spatial : Collèges du district d'El Oued, province d'El Oued. Champ d'application temporel : Notre étude s'est étendue du 15 février à la première quinzaine d'avril. Méthodologie : Descriptive. Outils d'étude : Questionnaire. Résultats : • La mixité a un impact négatif sur les performances des élèves en éducation physique et sportive (EPS) en terminale. • La mixité a un impact négatif sur les performances des élèves en EPS en terminale. Suggestions et recommandations : • Il est nécessaire de veiller aux cours d’éducation physique et sportive en limitant la mixité. • Réfléchir au programme hebdomadaire des cours d’éducation physique et sportive en regroupant les élèves pour former des groupes d’hommes et de femmes. • Tenir compte du calendrier des activités en classe pour chaque sexe afin d’aider les enseignants dans leur performance.
دراسة ميدانية ببعض متوسطات مدينة الوادي
Keywords: الاختلاط; التربيةالبدنيةوالرياضية; الطورالمتوسط; الأداءالبيداغوجي; الأستاذ (المعلم; التلميذ; Mixed learning; Physical Education and Sports; Intermediate Stage; Pedagogical Performance; The teacher; The Student; Apprentissage mixte; Éducation physique et sportive; Niveau intermédiaire; Performance pédagogique; L'enseignant (professeur; L'élève